Kebijakan Penegakan Hukum Pidana dalam Penanggulangan Perjudian Online Ditinjau dari Undang–Undang Republik Indonesia No.19 Tahun 2016 tentang Informasi dan Transaksi Elektronik - Luntungan, Benjamin Lemta; Sahid, Muhammad (Advokasi Hukum & Demokrasi (AHD), 2024)
This journal is titled Criminal Law Enforcement Policies in Combating Online Gambling Reviewed from the Republic of Indonesia Law Number 19 of 2016 concerning Information and Electronic Transactions. The rapid technological advancements today provide a great opportunity for criminals to commit crimes. Online gambling offenses have now entered the Internet world, known as online gambling. To reduce the level of criminality in online gambling, it is necessary to understand the law enforcement policies in combating online gambling offenses and the obstacles law enforcement face in addressing these crimes. This journal uses a descriptive normative legal research method, which aims to describe rather than test hypotheses. There are two approaches to combating online gambling: preventive measures involve providing warnings and monitoring the online world using the Internet, while the second approach, repressive measures, involve capturing, processing, taking to court, and imposing criminal sanctions in accordance with Article 45 paragraph (2) of the ITE Law, Article 303, and Article 303 bis of the Criminal Code. Based on the research findings, the author suggests: 1. The need to enhance law enforcement capabilities by upgrading IT-based technological knowledge. 2. Law enforcement officials are encouraged to be more proactive in combating online gambling offenses. In the case of online gambling, authorities can potentially block online gambling sites on a large scale, which would help minimize existing issues.